IMPLEMENTASI LABORATORY TRAINING SEBAGAI SOLUSI PEMBELAJARAN DIKOTOMIS - M. Bakir (PEDAGOGIK : JURNAL PENDIDIKAN, 2017)
This article is aimed to introduce the possible implementation of laboratory training in order to reduce a dicotomic based learning in Islamic education. Laboratory training assumes that first-hand experience in observation and manipulation of the materials of science is superior to other methods of developing understanding and appreciation. Laboratory training is also frequently used to develop skills necessary for advanced study and research. During the binarary opposition between West and East, between Islam and non-Islam, the educational institution needs a empircal ground of laboratory training as useful ways to provide the learners and educators attitudes and practical experiments to understand the possible effects of that dicotomy. This study further argues that laboratory training is to make sure that students are encouraged to have religious humanism as a philosophical basic of the Islamic teaching.